State and local taxation : (J. Ross Pub., 2004)
Written by a team of CPAs, professors, and tax lawyers with over 100 years of combined experience, this book offers new and keen insights into state and local taxation. The authors draw upon numerous real-life examples to identify and explain the fundamental principles of state and local taxation and how to incorporate these principles into strategic business planning. Designed with both the professional and college student in mind, the text follows the AICPA/ATA Model Tax Curriculum